PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA MELALUI AKTIVITAS RIIL - Boedhi, Nico Radityo; Ratnaningsih, Dewi (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
This study examines the impact of audit quality on Real Earnings Management (REM). Real earningsÃ‚Â management is defined as management actions that deviate from normal business practices, undertaken withthe primary objective of meeting certain earnings thresholds (Roychowdhury, 2006). One proxy is taken for realÃ‚Â earnings management, while abnormal operating cash flows and proxy for audit quality are taken as the size ofÃ‚Â audit firm. Research samples are selected from the population of manufacturing companies listed in Bursa EfekÃ‚Â Indonesia from year 2007 to 2011. Sample criteria is companies which have strong incentive to engage in realÃ‚Â earnings management and 126 companies are selected. Multiple Regression Model has been applied for dataÃ‚Â analysis. It is found that impact of audit quality on real earnings management is positive. This result concludesÃ‚Â that audit quality is not a warranty that a companyÃ¢â‚¬â„¢s financial statement is free from earnings management.Keywords: audit quality, earnings management, real earnings management, abnormal cash flow operation.